A sequential evaluation of left ventricular function in asymptomatic and symptomatic patients with chronic severe aortic regurgitation - Sarembock, Ian J (Division of Cardiology, 2017)
The optimal timing of valve replacement surgery in chronic severe aortic regurgitation (AR) has remained a major clinical problem in the management of these patients. Although the onset of symptoms is the generally accepted indication for aortic valve replacement (AVR), the unpredictable development of pre-symptomatic left ventricular (LV) dysfunction as a result of prolonged volume overload has resulted in numerous reports attempting to formulate a risk profile for these patients. Although aortic root and LV cineangiography have been the "gold standard" for defining the severity of AR and its effect on LV performance, serial follow-up by these means is impractical. More recently numerous non-invasive measures of LV size (echocardiogram) and function both at rest and on exercise (echocardiogram and equilibrium radionuclide angiocardiography., ERNA) have been serially utilised~ In these endeavours, the thinking has been clouded by a tendency to equate these two measures and failing to appreciate that apparent preoperative LV dysfunction (particularly on exercise) may be rapidly reversible by AVR and the consequent changes in LV loading conditions. This study was a prospective, sequential evaluation of left ventricular function using both non-invasive and invasive techniques in symptomatic and asymptomatic patients with isolated chronic, severe (4+) AR at cardiac catheterisation. The aims of the study were to (I) Identify differences in the clinical, echocardiographic, resting and exercise haemodynamic and I radionuclide measures of left ventricular function in symptomatic and asymptomatic patients with chronic severe A.R. with particular reference to the incidence of presymptomatic development of left ventricular dysfunction. (II) Critically evaluate the role of exercise stress (both isotonic and isometric) in the assessment of patients with chronic severe A.R. (III) Evaluate the influence of time (sequential studies) on the haemodynamic burden in asymptomatic patients. (IV) Study the impact of successful aortic valve replacement on the reversibility of abnormal pre-operative LV function in an attempt to predict which patients would benefit from this therapeutic intervention and whether operation for symptoms alone is the correct clinical practice.